Sharing CD4+ T Cell Loss: When COVID-19 and HIV Collide on Immune System - Peng, Xiaorong; Ouyang, Jing; Isnard, Stéphane; Lin, John; Fombuena, Brandon; Zhu, Biao; Routy, Jean-Pierre (Frontiers in Immunology, 2020)
COVID-19 is a distinctive infection characterized by elevated inter-human transmission and presenting from absence of symptoms to severe cytokine storm that can lead to dismal prognosis. Like for HIV, lymphopenia and drastic reduction of CD4+ T cell counts in COVID-19 patients have been linked with poor clinical outcome. As CD4+ T cells play a critical role in orchestrating responses against viral infections, important lessons can be drawn by comparing T cell response in COVID-19 and in HIV infection and by studying HIV-infected patients who became infected by SARS-CoV-2. We critically reviewed host characteristics and hyper-inflammatory response in these two viral infections to have a better insight on the large difference in clinical outcome in persons being infected by SARS-CoV-2. The better understanding of mechanism of T cell dysfunction will contribute to the development of targeted therapy against severe COVID-19 and will help to rationally design vaccine involving T cell response for the long-term control of viral infection.